Coup d'état and access to electricity in sub-Saharan Africa - Therese E. Zogo; Christophe Martial Mbassi; Simplice Asongu (African Governance and Development Institute (AGDI), 2024)
This paper assesses the effects of coups on access to electricity in Sub-Saharan Africa (SSA). The study covers a sample of 40 sub-Saharan African countries over the period 1980-2017. The econometric approach employed is the generalized method of moments (GMM). While the extant literature has established that political instability can have both positive and negative effects on access to basic public goods and services, the present study finds that coups significantly reduce access to electricity in SSA. This effect is the same regardless of the type of coup, notably: successful, failed, military or civilian coups. Thus, coups are not conducive for the establishment of real democratic transitions in the region which inter alia, are necessary to promote development outcomes such as access to electricity.
Keywords: D74; H41; 330; Coups d'état; Access to electricity